2013
DOI: 10.1002/lary.24201
|View full text |Cite
|
Sign up to set email alerts
|

Effective embryoid body formation from induced pluripotent stem cells for regeneration of respiratory epithelium

Abstract: Based on the varying suspension times and cell numbers with the ALI method, this study presented effective conditions for EB formation from iPS cells for regeneration of respiratory epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Embryoid bodies (EBs) were formed from tdTomato-labeled iPSCs in suspension culture over a period of 5 days in Knockout DMEM supplemented with 10% Knockout Serum Replacement (KSR) (Gibco), as described previously (Figure 1). 16 Briefly, iPSCs per 1 EB were seeded at a density of 1000 cells/well in low-adhesion 96-well plates. The EBs were then transferred to gelatin-coated Transwell inserts in 12-well plates (0.4-μm pore, 12-mm diameter, polyester; 4 EBs per well; Corning Inc, Corning, New York, USA) and cultured in serum-free differentiation medium comprising Knockout DMEM supplemented with 10% KSR, 100 ng/mL activin A, and 100 ng/mL basic fibroblast factor.…”
Section: Methodsmentioning
confidence: 99%
“…Embryoid bodies (EBs) were formed from tdTomato-labeled iPSCs in suspension culture over a period of 5 days in Knockout DMEM supplemented with 10% Knockout Serum Replacement (KSR) (Gibco), as described previously (Figure 1). 16 Briefly, iPSCs per 1 EB were seeded at a density of 1000 cells/well in low-adhesion 96-well plates. The EBs were then transferred to gelatin-coated Transwell inserts in 12-well plates (0.4-μm pore, 12-mm diameter, polyester; 4 EBs per well; Corning Inc, Corning, New York, USA) and cultured in serum-free differentiation medium comprising Knockout DMEM supplemented with 10% KSR, 100 ng/mL activin A, and 100 ng/mL basic fibroblast factor.…”
Section: Methodsmentioning
confidence: 99%
“…AT-2 cells or lung progenitor cells have been derived from human or mouse iPSCs and embryonic stem cells (ESCs) in several studies either through embryoid body (EB) formation or by using differentiation medium. Furthermore, administration of these iPSC-derived cells to mouse models of LPS-induced lung injury, bleomycininduced lung injury, and hyperoxia-induced lung injury has been shown to reduce injury, promote repair, and improve lung function [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Therefore, iPSC-derived cells are considered to have therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%
“…Induced pluripotent stem cells (iPSCs), which are obtained by introducing Yamanaka factors into differentiated somatic cells, display self-renewal properties and pluripotency [27]. AT-2 cells or lung progenitor cells have been derived from mouse iPSCs or embryonic stem cells (ESCs) in several studies either through embryoid body (EB) formation or by using differentiation medium, and the therapeutic potential of the iPSC-derived cells has also been reported [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. However, no study thus far has reported the in vitro differentiation of iPSCs into BASCs, and the therapeutic potential of BASCs remains unclear.…”
Section: Introductionmentioning
confidence: 99%